Islamic Center Di Rengat Dengan Pendekatan Arsitektur Melayu Indragiri Hulu - Aliddra, David; Susilawati, Mira Dharma; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Rengat is the capital of Indragiri Hulu Regency. The majority of the population in Indragiri Hulu Regency is Malay and is Muslim. At present, the people of Indragiri Hulu Regency experience a decline in terms of faith and are far from Islamic values. This can be seen from the many problems that have occurred in Indragiri Hulu Regency, such as immoral acts, murder, robbery and gambling. All problems have even deviated from the teachings of Islam. So that there needs to be a container in the form of an Islamic Center in order to reduce these problems. The design method used is the results of field surveys, documentation, analysis of qualitative data and quantitative data. The approach to design the Islamic Center used is the Indragiri Hulu Malay Architecture which focuses on the Architecture of the Indragiri Royal Palace. The concept of the Islamic Center is Hablum Mina Allah, Hablum Mina Annas, Hablum Mina Alam. The results of this design obtained the design of the Islamic Center not only serves as a place of worship, but as a place of study, a center for development, research and development, Islamic consulting centers, as well as places of education in Islamic contexts such as qur'an education places , seminars, skills training, talent development and creativity.Keywords: Indragiri Hulu, Islam, Islamic Center, Indragiri Hulu Malay Architecture.